2004
DOI: 10.1159/000080590
|View full text |Cite
|
Sign up to set email alerts
|

No Relationship between Subchronic Fluoride Intake and DNA Damage in Wistar Rats

Abstract: Fluoride has been widely used in dentistry because it is an effective caries prophylactic agent. However, excess fluoride may represent a hazard to human health, especially by causing injury on the genetic apparatus. Genotoxicity tests form an important part of cancer research and risk assessment of potential carcinogens. In the current study, the potential DNA damage associated with exposure to fluoride was assessed by the single cell gel (comet) assay in peripheral blood, oral mucosa and brain cells in vivo.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
0
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 40 publications
(28 reference statements)
3
11
0
2
Order By: Relevance
“…Our results clearly demonstrated that fluoride at all concentrations tested did not contribute to the damage of DNA. Our results are consistent with other studies [Li et al, 1987;Ribeiro et al, 2004a]. On the other hand, some researchers reported that fluoride inhibits both protein and DNA synthesis and induces DNA lesions through apoptosis in cultured mammalian cells [Wang et al, 2004;Kubota et al, 2005;Satoh et al, 2005].…”
Section: Discussionsupporting
confidence: 93%
“…Our results clearly demonstrated that fluoride at all concentrations tested did not contribute to the damage of DNA. Our results are consistent with other studies [Li et al, 1987;Ribeiro et al, 2004a]. On the other hand, some researchers reported that fluoride inhibits both protein and DNA synthesis and induces DNA lesions through apoptosis in cultured mammalian cells [Wang et al, 2004;Kubota et al, 2005;Satoh et al, 2005].…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, current literature about the genotoxic potential of fluoride in various cells and/or tissues is contradictory. Studies have shown that fluoride does not induce DNA damage [5355], whereas other studies have observed fluoride-induced DNA damage in rat and human cells [52,56,57]. The possible mechanisms of fluoride-induced DNA damage are that (1) fluoride directly attacks the free amine groups present in DNA or (2) fluoride acts indirectly through free radicals to create DNA adducts at hydrogen bonds [58].…”
Section: Discussionmentioning
confidence: 99%
“…It is generally accepted correlation between genotoxic and carcinogenic effects of a variety of chemicals (18). Whether the DNA damage is repaired or persists is important to the fate of cells targeted by chemical carcinogens (33).…”
Section: Discussionmentioning
confidence: 99%